Paremiae and Phraseological Units in the Speech of Characters in the Novel “The Geographer Drank His Globe Away” by A. Ivanov - Anna Alexandrovna Vasilyeva (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
The article is devoted to the study of language units, describing linguistic personality. The purpose of this article is to review the functioning of precedent texts existing in paremiological space. The analysis of domestic and foreign phraseology and paremiology identifies and analyses the units related to paremiae. The article used the method of verbal portraying, allowing to describe the linguistic identity of a novel character.